CLAW: A Multifunctional Handheld Haptic Controller for Grasping, Touching, and Triggering in Virtual Reality - Choi, Inrak; Ofek, Eyal; Benko, hrvoje; Sinclair, Mike; Holz, Christian (CHI 2018, 2018)
CLAW is a handheld virtual reality controller that augments the typical controller functionality with force feedback and actuated movement to the index finger. Our controller enables three distinct interactions (grasping virtual object, touching virtual surfaces, and triggering) and changes its corresponding haptic rendering by sensing the differences in the user’s grasp. A servo motor coupled with a force sensor renders controllable forces to the index finger during grasping and touching. Using position tracking, a voice coil actuator at the index fingertip generates vibrations for various textures synchronized with finger movement. CLAW also supports a haptic force feedback in the trigger mode when the user holds a gun. We describe the design considerations for CLAW and evaluate its performance through two user studies. The first study obtained qualitative user feedback on the naturalness, effectiveness, and comfort when using the device. The second study investigated the ease of the transition between grasping and touching when using our device.